EXPLORING INCARCERATED STUDENT PRISONERS’ EXPERIENCES WITH DISTANCE MODE OF STUDYING - Vimbi Petrus Mahlangu (CV. RADJA PUBLIKA, 2024)
The case study aimed to investigate the experiences of incarcerated students engaged in distance learning and the university's support efforts. Its objective was to guide future research and initiatives for better supporting this student group. The central inquiry was focused on understanding the challenges and benefits faced by incarcerated students participating in distance education. Through qualitative methods, data were gathered via in-depth interviews with 12 incarcerated students enrolled in a Namibian correctional facility's distance education program. The findings highlighted key themes such as the flexibility and independence provided by distance learning, enabling students to manage academic commitments alongside prison duties. Challenges noted included limited access to technology, internet disruptions, and difficulties in accessing learning materials. Furthermore, participants emphasized how distance education positively influenced their personal growth, skills development, and prospects for reintegrating into society post-incarceration. The study underscores the necessity of customizing distance education initiatives to meet the unique needs and constraints of incarcerated individuals, acknowledging the transformative potential of education within the prison environment.